Analisys of The Quality of Customer Service Satisfactory of Baitul Maal Wattamwil (BMT) Tamzis at Daerah Istimewa Yogyakarta and Jawa Tengah - Agus Siswanto; Abdul Choliq Hidayat (Forum Inovasi Bisnis dan Manajemen, 2019)
The research aim was to analyse the quality of customer service satisfactory of BMT Tamzis at Daerah Istimewa Yogyakarta and Jawa Tengah, as the syariah finance, who has 33 (thirty three) branchs, and its headquarter at Wonosobo, Jawa Tengah. It has at least 2.000 customers in 2018. BMT Tamzis needs some feedback in order to increase their quality of customer service satisfactory as high as possible to reach optimum level, and fulfill qualification of succeed finance business. This research wanted to measure the up dated customer service satisfactory and gave feedback to BMT Tamzis. The research method used quantitative approach to primary data of customer questioneer and scondary data of BMT Tamzis’s headquarter. The questioneers had distributed to customers by proporsional random sampling about 330 examplars, returned back about 320 examplars, and than have been calculated by SPSS method version 10.0. The result research was customer satisfactory perception toward BMT Tamzis reached good and significance level at all branchs, at point 4.031 root mean at 1 until 5 Likert scale. They favored assurance dimension at point 4.215, and than tangibles (3.990), responsiveness (3.989), reliability (3.976), and emphaty (3.986). To be adviced that all branch leaders must increase giving their services until reach the highest level of all dimensions, that are : tangibles, responsiveness, reliability, emphaty, dan assurance.